FACTOR ANALYSIS OF EYE FAILURE COMPLAINTS ON COMPUTER USING WORKERS IN THE K3L ROOM PT PLN (PERSERO) UPK NAGAN RAYA - Amalia Amalia; Siti Maisyaroh Fitri Siregar (RADJA PUBLIKA, 2022)
Eye fatigue is an eye discomfort caused by excessive use of the sense of sight when working for long periods of time accompanied by uncomfortable viewing conditions caused by poor lighting. The purpose of this study was to determine and analyze the factors associated with eye fatigue in computer users. In this study the authors conducted research using descriptive qualitative methods, namely by conducting interviews and observations. The data used are primary data obtained from interviews and observations of 5 workers in the K3L room of PT PLN (Persero) UPK Nagan Raya and secondary data obtained by collecting all data related to the study. The results show that among the variables of age, duration of computer use, monitor distance, eye rest and lighting, there are two factors that can be said to be the cause of eye fatigue, namely the monitor distance and lighting variables. The conclusion is that there is a relationship between monitor distance and lighting with eye fatigue, but there is no relationship between age, duration of computer use and eye rest in computer users. It is recommended for companies to provide training to workers on preventing eye fatigue.